The reality of the technical skills necessary to carry out scientific research among the trainees of the Technical College for Girls in Tabuk, Saudi Arabia - Alamrani, Fatimah Salem; Aljuhani, Ameera Maitiq; Asiri, Amal Ahmed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the reality of the technical skills necessary to carry out scientific research among the trainees of the College of Technical in Tabuk, Saudi Arabia. The study also aimed to identify the obstacles facing female trainees of the Technical College in the city of Tabuk related to the technical skills necessary to carry out scientific research. and to identify the attitudes of the trainees of the College of Technical in Tabuk towards the implementation of scientific research using technology and the Internet. The study followed the descriptive approach with a study sample that consisted of (78) female trainees and the questionnaire was used as the main tool. The study reached the following results: The Technical College trainees’ possession of the technical skills necessary to carry out scientific research came to a large degree, with an arithmetic average of (4.02 out of 5) and a relative weight of (80.4%). The attitudes of the technical college trainees towards technical skills were highly significant with an arithmetic mean of (4.12) and a relative weight of (82.5%). And that there is a moderate degree of obstacles facing the trainees in the College of Technical related to the implementation of scientific research, with an arithmetic mean of (2.92) and a percentage of (58.4%). The study recommended providing support, motivation, and encouragement to female trainees while they are going through the scientific research experience for the first time and the necessity of holding training courses and workshops aimed at developing trainees’ skills to use the Internet in conducting scientific research.